Social exclusion and suicide intention in Chinese college students: a moderated mediation model - Zhu, Juncheng; Xie, Pei; Zhang, Xingyu (Frontiers in Psychology, 2024)
Given the growing incidence rates of suicide among college students and the potential lifelong consequences of suicide, it is imperative to better understand the factors that reduce the rates at which college students in a clinical sample engage in suicide. This study examines the relationship between social exclusion and suicide intention, the mediating effect of depression, and the moderating effect of meaning in life. Two hundred and ninety-nine Chinese college students, aged from 18 to 22 years (56.86% female, M age = 20.14, SD = 1.27) completed questionnaires assessing their social exclusion, suicide intention, depression, and meaning in life. The result revealed that social exclusion was positively associated with suicide intention, and depression mediated this relationship. In addition, this mediating effect of depression was moderated by meaning in life. That is, the mediation effect was stronger for students with a higher level of meaning in life. These findings provide educational suggestions for preventing and intervening in suicide intention among college students.